Analysis of Physical Fitness of Students Living in Boarding Schools and Non Boarding Schools - Dintuqatih, Nisavinea; Setya Rahayu; Fajar Awang Irawan (Universitas Negeri Semarang, 2025)
This research aims to analyze the physical fitness of students who live in Islamic boarding schools and non-Islamic boarding schools. The research method used in this research is a quantitative approach with a survey design. The research subjects used in this research were MA Matholi'ul Huda Bugel Kedung Jepara students. The sampling technique uses total sampling. Data collection by observation, tests and documentation. Quantitative data analysis consisted of normality tests, hypothesis testing using SPSS version 26 software. The results of the research showed that the physical fitness level of all female students was in the good category. The Physical Fitness Score of the Non-Pottage TKPN = 378.53 is higher than that of the Pondok Group which is = 336.51. The limitation of this research is that it only involves MA Matholi'ul Huda Bugel Kedung Jepara female students, so the results cannot be generalized to all madrasa female students or schools in other areas. Based on the research results and existing limitations, the recommendation for further research is sample expansion, with a larger and more diverse sample from various madrasas or schools in other areas to increase the generalization of the research results. Then physical activity, taking more detailed and comprehensive measurements regarding the daily physical activity carried out by female students, both at the boarding school and outside the boarding school. Develop and test fitness programs to be implemented in Islamic boarding schools and schools to improve female students' physical fitness and conduct long-term research to see changes in female students' fitness and the factors that influence them.